Physiological Disorders and Fruit Quality Attributes in Pomegranate: Effects of Meteorological Parameters, Canopy Position and Acetylsalicylic Acid Foliar Sprays - Drogoudi, Pavlina; Pantelidis, Georgios E.; Vekiari, Stavroula A. (Frontiers in Plant Science, 2021)
Meteorological parameters and occurrences of cracking (CR), russeting (RS) and sun scald (SS) symptoms were monitored in a pomegranate cv. ‘Wonderful’ orchard planted in a W-E orientation, during a three year study. Moreover, the effefficacyects of preharvest foliar applications sprays with acetylsalicylic acid (ASA;, 0.5 mM or 1.0 mM), applied biweekly 4-6 times, on yield and fruit quality attributes were also evaluated in a two year study. Damages from CR and RS were very prominent in the experimental orchard and fFruit from the N-side of canopy had greater CR and RS damages, whereasile SS symptoms were lower, compared with the S-exposed part of canopy. The N-side of canopy had also substantially lower fruit number and yield, suggesting for an important role of light on bisexual flower formation and/or fruit set. Following the occurrences in CR and RS during the fruit maturation period, it was found that temperature fluctuations were was the main cause. The presence of RS damages may also be related with increased relative humidityRH and water movement as suggested by symptoms were higher in years with higher values, in the N-side of canopy and often occurred the greater occurrence in the exposed and stylar end of fruit. The ASA treatment substantially reduced RS by up to 57%, improved the peel red coloration while anthocyanin, antioxidant capacity and soluble solid contents in juice were higher. Foliar sprays with ASA treatment did not affect yield, but induced a trend of bigger sized fruit. In conclusion, planting in a N-S row orientation and selecting an orchard plantation site with a minimum out temperature fluctuations and lowhigh relative humidity during the fruit ripening period are measures to control CR and RS in pomegranate. ASA foliar applications proved to have beneficial effects on juice antioxidant contents, but more importantly on fruit appearancecould be a promising method to control RS damages and improve fruit quality with health beneficial effects in pomegranate.